Pengaruh Metode Snowball Throwing terhadap Hasil Belajar Pendidikan Agama Islam Kelas 5 SD Pembangunan Laboratorium UNP - Annisa, Windi Rizky; Satria, Rengga (ALSYS, 2024)
This research was conducted because there are still students who experience difficulties in achieving good learning achievements in Islamic Religious Education subjects. The aim of this research is to evaluate the effect of the Snowball Throwing method in the 5th grade at UNP Laboratory Development Elementary School. The type of research is quasi-experimental. There are 36 students in class 5, each with 18 students in class 5A as the control class and 18 students in class 5B in the experimental class. Saturated sampling technique was used in the sampling process. Preliminary and final ability tests were used to collect research data. The results showed that the average score for the experimental class was 87.22. The learning objectives given in the form of a final exam are superior to the control class with a class average of 70.55. We can conclude that the learning outcomes of 5th grade elementary school students are influenced by the Snowball Throwing learning paradigm.